Development of competences in the formation of production engineers: a contribution from teaching physics - Boesing, Ivan Jorge; André da Rosa, Jarbas; Jung, Carlos Fernando; Sporket, Frederico (Revista Gestão da Produção Operações e Sistemas, 2008)
This paper presents the results of a teaching-learning experiment to optimize the process of Physics Learning, assisting in developing Industrial Engineering skills of students in southern Brazil. The experiment was elaborated by integrating the following methodological principles of the following proposals: Problem-Based Learning (PBL), Problem-Solving Learning and Discovery Learning. Prototypes of new products were obtained as results, verifying that the actual exposure of students to the activities of Physics Teaching can assist in training professional skills, aimed at the future development of technological innovations. Key-words: Problem-Solving; PBL; Learning; Teaching; Physics; Engineering.